Toward a Holistic Rating System: An Attempt to Expand the Boundaries of Building Sustainability Using SDGs - Vitale, Pierluca; Alfano, Vincenzo; Pastore, Tommaso; Menna, Costantino; Maffettone, Pietro; Asprone, Domenico (Frontiers in Built Environment, 2021)
Several frameworks have been developed for mitigating the environmental impact of human activities. Among them, possibly the most forward-thinking are the Sustainable Development Goals (SDGs) set out in UN Agenda 2030, which are often cited by stakeholders at various levels. Nevertheless, when it comes to policy tools, defining goals relating to sustainability is not straightforward. In this contribution, we use a mathematical framework to compare the goals of Agenda 2030 with the assessments possible with three different building-rating systems, BREEAM, LEED and ITACA. Our results show that these tools address sustainability very differently to the intentions of the SDGs. However, a number of minor changes could easily make the assessments produced by these evaluation systems on this issue more complete.